Tribological characterisation and modelling for the fused deposition modelling of polymeric structures under lubrication conditions - He, Feiyang; Xu, Chenyan; Khan, Muhammad (MDPI, 2023)
In recent years, additive manufacturing technology, particularly in plastic component fabrication, has gained prominence. However, fundamental modelling of the influence of materials like ABS, PC, and PLA on tribological properties in fused deposition modeling (FDM) remains scarce, particularly in non-lubricated, oil-lubricated, and grease-lubricated modes. This experimental study systematically investigates the effects of material type, lubrication method, layer thickness, and infill density on FDM component tribology. A tribology analysis is conducted using a TRB3 tribometer. The results indicate a coefficient of friction (CoF) range between 0.04 and 0.2, generally increasing and decreasing with layer thickness and filler density. The lubrication impact hinges on the material surface texture. The study models the intricate relationships between these variables via full-factor analysis, showing a strong alignment between the modelled and measured friction coefficients (an average error of 3.83%). Validation tests on different materials affirm the model’s reliability and applicability.
Keywords: 3D printing; ABS; PC; PLA; coefficient of friction; wear rate; lubrication; infill density; layer thickness